Exploring the therapeutic potential of H1-antihistamines in endometriosis—A gene regulation-based perspective - Mantha, Kameswara Bharadwaj; Gajendran, Mohan Kumar (Frontiers in Medicine, 2025)
IntroductionRecent studies emphasize the role of immune dysregulation and inflammation in endometriosis (ES). While hormonal therapy remains the primary treatment, emerging research is exploring synergistic approaches that target inflammation. In this study, we investigate the potential of H1-antihistamines (H1-As) in ES management from a gene-regulation viewpoint.MethodsWe perform differential gene expression analysis on two gene-sequencing datasets from ES patients, with a primar focus on inflammatory signaling [nuclear factor-kappa B (NF-κB), tumor necrosis factor (TNF), and cytokine–cytokine receptor] and histamine synthesis and metabolism (HSM) pathways, considering disease severity and hormonal therapy usage.Results & DiscussionConsistent with the literature, our findings highlight the dysregulation of several genes involved in pro-inflammatory pathways, including interleukins (ILs), cyclooxygenase-2 (COX-2), chemokine ligands, cellular adhesionmolecules, and neuroangiogenesis. We also note dysregulation of genes in the HSM pathway, indicative of a microenvironment that favors histamine availability and inflammatory persistence through enhanced histamine synthesis and reduced breakdown, as well as a reduced potential to clear reactive aldehyde species. We also find that hormonal therapy minimally affects the dysregulation of the majority of pro-inflammatory and histaminic pathway genes, and their amplified dysregulation is noted in early stage disease. By placing our findings in the context of existing evidence on histamine-mediated modulation of inflammatory pathways via the H1 histamine receptor (HRH1), we present a comprehensive discussion on the potential therapeutic value of H1-As in ES management due to their anti-inflammatory and mast-cellstabilizing properties.